2014
DOI: 10.1111/ecaf.12083
|View full text |Cite
|
Sign up to set email alerts
|

The Privatisation of the UK Railway Industry: An Experiment in Railway Structure

Abstract: The British rail network was privatised in the mid‐ to late 1990s. However, the sector was heavily regulated and not permitted to evolve according to market processes. Indeed, the government imposed a complex and fragmented structure on the industry which ran counter to traditional railway practices. As a consequence, economies of scale and scope were lost, while transaction costs were increased. There was a negative impact on costs and safety. Given the disappointing outcomes, there is a strong case for refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Based on the literature study shown in Table 2, most of the operation ranges from 30 to 50 years. Some countries, such as the UK and Netherlands, where the infrastructure manager (IM) exists to manage the infrastructure, private parties are responsible only for the train operation [40]. While in other countries, the private parties only are given the responsibility to provide infrastructure and maintain it in a certain period.…”
Section: Public-private Partnership In Railway Projectsmentioning
confidence: 99%
“…Based on the literature study shown in Table 2, most of the operation ranges from 30 to 50 years. Some countries, such as the UK and Netherlands, where the infrastructure manager (IM) exists to manage the infrastructure, private parties are responsible only for the train operation [40]. While in other countries, the private parties only are given the responsibility to provide infrastructure and maintain it in a certain period.…”
Section: Public-private Partnership In Railway Projectsmentioning
confidence: 99%
“…A similar trend occurred in Japan, where the railways' capture of passenger services fell from over 80% in 1955 to 38.5% in 1985; its decline in share of freight market declined from 52.9% to 5 % over this same period (Mitzutani 1999). In the decades leading up to privatization, British Rail also saw a decline in its share of the transportation market and a rise in its dependence on the state for regular financial support (Wellings 2014).…”
Section: Unbundling the Railways: The Question Of Vertical Separationmentioning
confidence: 99%
“…Eventually, in 1991, ownership and operations of all high-speed railways in Japan were sold to three of the passenger-service oriented Japanese Railway Companies . British Rail was both vertically and horizontally separated by establishing the company Railtrack for infrastructure management and creating 25 companies for passenger train operations and 3 companies dedicated to freight operations (Wellings 2014;Preston and Robins 2013).…”
Section: Campos (2001) Attributes the Decline In Railways' Transport mentioning
confidence: 99%
See 2 more Smart Citations